2007
DOI: 10.1258/147775007781029500
|View full text |Cite
|
Sign up to set email alerts
|

Is 'inconsistency' in research ethics committee decision-making really a problem? An empirical investigation and reflection

Abstract: Research Ethics Committees (RECs) are frequently a focus of complaints from researchers, but evidence about the operation and decisions of RECs tends to be anecdotal. We conducted a systematic study to identify and compare the ethical issues raised in 54 letters to researchers about the same 18 applications submitted to three RECs over one year. The most common type of ethical trouble identified in REC letters related to informed consent, followed by scientific design and conduct, care and protection of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…Their systematic study of RECs' decisions revealed some consistency across committees in the things which they see as requiring attention, such as consent procedures, but also, as reported above, some variability in the types of 'ethical troubles' they identify. However, in contrast to our interviewees, Angell et al 15 contend that inconsistencies across RECs should not necessarily be seen as problematic, but should be seen as a strength -as a marker of the inevitable variability and the flexible nature of moral judgements.…”
Section: Discussioncontrasting
confidence: 77%
“…Their systematic study of RECs' decisions revealed some consistency across committees in the things which they see as requiring attention, such as consent procedures, but also, as reported above, some variability in the types of 'ethical troubles' they identify. However, in contrast to our interviewees, Angell et al 15 contend that inconsistencies across RECs should not necessarily be seen as problematic, but should be seen as a strength -as a marker of the inevitable variability and the flexible nature of moral judgements.…”
Section: Discussioncontrasting
confidence: 77%
“…In other papers15 16 we have reported on the ethical issues raised by RECs in their letters about these applications; in this paper, we were concerned with the issues that were not (strictly speaking) “ethical” in character, but instead referred to various kinds of process errors which RECs perceived as having been made by the applicants (though we recognise that such errors may have ethical dimensions or consequences). We are using the term “process error” here to describe lapses in paperwork, application processes or management issues.…”
Section: Resultsmentioning
confidence: 99%
“…Our framework was generated initially through close inspection and comparison across the texts of letters used in a previous study,15 but was modified extensively in response to the new data in this project. Explicit specifications were devised to aid data assignment to analytic categories, a process which was facilitated by the use of QSR N6 software (QSR International, Melbourne, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…However, as DeVries and Forsberg (2002) pointed out, the rise of multicenter research alleviated the need for mock applications, and instead, researchers wrote about their first-hand experience of submitting the same application to multiple committees and receiving inconsistent responses; Edwards, Stone, and Swift (2007) reported on twenty-six articles describing such discrepancies in ethics committee responses. The second type of method that has been used to examine decision-making of ethics committee members is analysis of letters from ethics committees to researchers following review of their ethics applications (Angell et al, 2007;Angell et al, 2008;O'Reilly et al, 2009). These studies also pointed to the variability of decisions made by ethics committees.…”
mentioning
confidence: 99%